DESIGN AND IN VITRO EVALUATION OF SUSTAINED RELEASE MATRIX TABLETS OF METFORMIN PRODUCED USING DETARIUM MICROCARPUM GUM - OKAFO, SINODUKOO EZIUZO; ALALOR, CHRISTIAN ARERUSUOGHENE; ORDU, JOHN IKECHI (International Journal of Applied Pharmaceutics, 2020)
Objective: The objective of this study was to evaluate sustained release matrix tablets of metformin formulated using Detarium microcarpum gum (DMG) as the matrix polymer. Methods: DMG was produced by acetone desolvation of the filtrate obtained by maceration of powdered seeds of Detarium microcarpum in distilled water. Metformin matrix tablets were prepared by direct compression technique using DMG or sodium carboxymethylcellulose (NaCMC) alone, or their combinations as the polymer matrix. The tablets were evaluated for hardness, friability, weight uniformity, drug content, swelling behaviour and in vitro dissolution. They were compared to a marketed product. Results: The results of the evaluation showed that the tablets had physical characteristics that were within the acceptable limits and were comparable to the marketed product. They include hardness (7.13±1.99 to 13.17±1.59 Kgf), friability (0.40 to 0.80%), and drug content (95.11 to 104.17%). Formulations MTF2 (30% DMG) and MTF6 (20% DMG and 10% NaCMC) showed good sustained release behaviour, as they released 75% of the drug within 7 to 9 h and 100% release in more than 12 h. Conclusion: DMG alone or with NaCMC was successfully used to formulate sustained release metformin matrix tablets that were comparable to the marketed product.